IMPLEMENTASI GERAKAN 15 MENIT MEMBACA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA DI SEKOLAH DASAR - Yudanti, Seni Tri; Masnunah, Masnunah; Syaflin, Sylvia Lara (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
The aim of this study was to examine the implementation of the 15-minute reading movement and its impact on students’ reading comprehension skills in elementary school. This study employed a descriptive qualitative method. The informants in this research were teachers and fifth-grade students, while the object of the study was the implementation of the 15-minute reading movement at SD Negeri 5 Talang Ubi. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the observation showed that 73.33% of the implementation of the 15-minute reading movement was categorized as good in supporting students’ reading comprehension skills. The interview results indicated that the school literacy movement has been well implemented and supported by adequate facilities and structured activities provided by the school. Furthermore, students’ reading comprehension skills were found to be good, as evidenced by their ability to understand the meaning or content of the texts they read.